Securing the feedstock procurement for bioenergy products: a literature review on the biomass transportation and logistics. (1st November 2018) - Ko, Sangpil; Lautala, Pasi; Handler, Robert M.
Abstract: The importance of transportation and logistics in the biomass supply chain has been recognized, yet the specific research on those topics has been limited. This paper reviews the peer-reviewed literature to assess the current challenges, trends, and ideas in the biomass transportation and logistics research. All papers were selected based on three English keywords: transportation, logistics, and biomass. We addressed literature statistics per research category and then discussed four criteria that significantly influence the viability of the supply chain: transportation/logistics cost, shipping distance, plant capacity, and system efficiency. A brief review of industry literature was also conducted to identify topics potentially absent from the peer-reviewed literature. The study findings included the great variability of values used in the literature, both related to the fixed and variable costs of transportation and to the optimal shipping distance based on logistics conditions. From transportation mode and plant capacity perspective, we found that studies have concentrated on improving system efficiency of truck transportation for smaller plants while large plants have received less attention. The research gaps included the seemingly poor fit of typical logistics and supply chain frameworks with biomass systems. There is also a lack of sustainable transportation cost model to account for economic, environmental, and social factors. Finally, there is a need to explore the effects of feedstock conversion and upgrading options to biomass transportation logistics (BTL) and to combine the BTL studies with long-term biomass sourcing strategies to mitigate supply variations. Highlights: This paper reviewed the articles related to the biomass transportation and logistics (BTL). The selected articles were summarized and analyzed according to the six review categories. We discussed four criteria that significantly influence the viability of the BTL. Several gaps/challenges were identified in the studies.